A detailed examination of the growth of CdSe thin films through structural and optical characterization - Yukselici, M. H.; Bozkurt, A. Asikoglu; Omur, B. Can (PERGAMON-ELSEVIER SCIENCE LTD, 2013)
Different thickness CdSe thin films were grown on glass substrates by physical vapor deposition and characterized by optical and structural investigations. Urbach energy related to the width of the optical absorption tail decreases from 430 meV for a film thickness of 50 nm to 200 meV for 450 nm. The film thickness dependent grain sizes were estimated by using effective mass model under quantum size effect from the shift of around 500 meV in the asymptotic absorption edge. The X-ray diffraction (XRD) pattern is consistent with CdSe hexagonal crystal structure which indicates crystal growth mode along c axis. XRD peaks broaden and shift depending on film thicknesses which are presumably due to strain and size effect. We observe both blue and red shift depending on thickness in Longitudinal Optical phonon frequency in Raman spectra with respect to that of the source CdSe powder which could also be due to strain on thin films and/or finite crystallite size. In this work we combine the results of optical absorption, Raman and XRD spectroscopies to study the evolution of grain size, strain and structural disorder depending on film thickness. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Thin films; Vapor deposition; X-ray diffraction; Crystal structure; Optical properties; SUBSTRATE-TEMPERATURE; SEMICONDUCTOR NANOCRYSTALS; LATTICE CONTRACTION; RAMAN-SCATTERING; QUANTUM DOTS; GLASS; SHIFTS; SIZE; Materials Science